2021
DOI: 10.1093/jxb/erab171
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal symbiosis primes the accumulation of antiherbivore compounds and enhances herbivore mortality in tomato

Abstract: Plant association with arbuscular mycorrhizal fungi (AMF) can increase their ability to overcome multiple stresses, but their impact on plant interactions with herbivorous insects is controversial. Here we show higher mortality of the leaf-chewer Spodoptera exigua when fed on tomato plants colonized by the AMF Funneliformis mosseae, evidencing mycorrhiza-induced resistance. In search of the underlying mechanisms, an untargeted metabolomic analysis through ultra-performance liquid chromatography tandem mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 77 publications
1
46
0
1
Order By: Relevance
“…Finally, AMF is commercialized as biostimulants in agriculture. These obligate biotrophs improve plant nutrient uptake and tolerance/resistance to multiple stresses, being able to protect the host plant against diverse pathogens and pests (Jung et al, 2012;Sanmartín et al, 2020;Rivero et al, 2021). AMF does not produce antibiotics, but compete with the pathogens for nutrients and colonization sites and boosts the defensive capacity of plants, leading to ISR (Pozo and Azcón-Aguilar, 2007;Jung et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, AMF is commercialized as biostimulants in agriculture. These obligate biotrophs improve plant nutrient uptake and tolerance/resistance to multiple stresses, being able to protect the host plant against diverse pathogens and pests (Jung et al, 2012;Sanmartín et al, 2020;Rivero et al, 2021). AMF does not produce antibiotics, but compete with the pathogens for nutrients and colonization sites and boosts the defensive capacity of plants, leading to ISR (Pozo and Azcón-Aguilar, 2007;Jung et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, AM enhances plant phenotypic plasticity, an important advantage in heterogeneous and changing environments where the precise allocation of limited resources between growth and stress resistance is critical for survival [15][16][17]. Mycorrhizal plants are usually more resistant to abiotic stresses such as drought, salinity, and heavy metal pollution [17][18][19], but AMF can also increase plant resistance/tolerance to biotic stresses by triggering the so-called mycorrhiza-induced resistance (MIR) against diverse root and foliar pathogens and pests [20][21][22][23][24][25][26][27][28]. In return, AMF require photosynthates and lipids from the plant to complete their life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…This interconnection between Plantago lanceolate with the AM fungus Funneliformis mosseae and the herbivore Mamestra brassica was studied by Qu et al. Surprisingly, in contrast to tomato (Rivero et al, 2021), they reported in their specific case a repression of JAmediated defense by AM fungi, underlining the complexity of the studied model under their selected conditions (symbiotic and pathogen partners, age of plants, light, soil P, JA treatments). Mycoparasitic Trichoderma fungi have been used as biocontrol agents (Guzmán-Guzmán et al, 2019).…”
Section: Editorial On the Research Topic Beneficial Microbes And The Interconnection Between Crop Mineral Nutrition And Induced Systemic mentioning
confidence: 94%